Computerized Assessment of Age Differences in Memory Beliefs. Issue 2 (October 2014) - Hertzog, Christopher; Lineweaver, Tara T.; Hines, Jarrod C.
Beliefs about memory play a role in older adults' concerns about aging and can influence their performance on memory tasks. Visual analog scales can capture beliefs about how aging affects memory in general (the General Beliefs About Memory Instrument [GBMI]) and one's own memory (the Personal Beliefs About Memory Instrument [PBMI]). Data were combined across four cross-sectional studies of adults who had completed the two measures, contrasting traditional paper-and-pencil versions of the questionnaires with newer computerized versions that use a computer mouse for visual analog scaling. This scaling method is easy to use and automates scoring of graphic rating scale responses. Adults of all ages produced GBMI responses reflecting their belief that memory declines with advancing age. Older adults' PBMI responses indicated that they perceived their memory ability more negatively than those of young adults and middle-aged adults. Adults of all ages were able to use the computerized questionnaires without difficulty, making these measures suitable for use in adult developmental research.